RESULTS OF OBSERVATIONS OF V1081 TAU AND A NEW EA TYPE VARIABLE STAR BD+23°770 IN THE TAURUS - Bryukhanov, I. S.; Vereshchagin, G. V. (Одеські астрономічні публікації, 2017)
The stars V1081 Tau = NSV 1702 and BD+23°440 (GSC 1832.1631) are found tobe EA-type eclipsing variables with the elements 2449215.51+1.0078 x E and 2448597.342+1.95558 x E based on 142 Ipv negatives of the "Betelgeuse" collection.